1993
DOI: 10.1093/brain/116.3.511
|View full text |Cite
|
Sign up to set email alerts
|

Rapid modulation of human cortical motor outputs following ischaemic nerve block

Abstract: The amplitudes of motor evoked potentials to transcranial magnetic stimulation from muscles immediately proximal to a temporarily anaesthetized (Bier's block) human forearm increase in minutes after the onset of anaesthesia and return to control values after the anaesthesia subsides. In order to determine the level at which the early modulation of human motor outputs takes place, we recorded maximal H reflexes, peripheral M responses, motor evoked potentials to transcranial magnetic stimulation, and motor evok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
1
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 276 publications
(143 citation statements)
references
References 0 publications
6
135
1
1
Order By: Relevance
“…62−65 Finally, and most closely related to the present issue, TMS over motor cortex has also been reported to induce a 'sense of movement' when actual motor responses were ischaemically blocked. 66,67 (Recently, the cortical origin of this kinaesthetic, body-part illusion has been questioned. 68 ) To the best of our knowledge, TMS has never evoked productive effects when applied to higher order association cortex, such as the temporo-parietal junction, temporal cortex or the prefrontal cortex.…”
Section: Combining Tms With Cognitive Neuroscience To Induce Obesmentioning
confidence: 99%
“…62−65 Finally, and most closely related to the present issue, TMS over motor cortex has also been reported to induce a 'sense of movement' when actual motor responses were ischaemically blocked. 66,67 (Recently, the cortical origin of this kinaesthetic, body-part illusion has been questioned. 68 ) To the best of our knowledge, TMS has never evoked productive effects when applied to higher order association cortex, such as the temporo-parietal junction, temporal cortex or the prefrontal cortex.…”
Section: Combining Tms With Cognitive Neuroscience To Induce Obesmentioning
confidence: 99%
“…One possible mechanism accounting for RMT lowering may involve changes in sodium channels (Chen et al, 1997;Ziemann et al, 1996), which have been implicated in some forms of plasticity (Halter et al, 1995). RMT was reduced after amputation (Chen et al, 1998;Cohen et al, 1991) but not after ischemic nerve block (Brasil-Neto et al, 1993;Ridding and Rothwell, 1997;Ziemann et al, 1998a), suggesting that changes in RMT may require long term deafferentation. This hypothesis is consistent with studies on rats with nerve lesions of different duration (Sanes et al, 1990).…”
Section: Motor Maps and Mep Recruitment Curvesmentioning
confidence: 99%
“…Learning new motor skills (Pascual-Leone et al, 1995) and performing skilled motor activities result in an expansion of the representation of the muscles involved in the task. Complete long term sensorimotor deafferentation, as in the case of limb amputation (Chen et al, 1998;Cohen et al, 1991;Kew et al, 1994;Ridding and Rothwell, 1997;Wu and Kaas, 1999) and peripheral nerve lesions (Rijntjes et al, 1997;Tinazzi et al, 1998), as well as short term deafferentation secondary to ischemic nerve block (Brasil-Neto et al, 1993;Ridding and Rothwell, 1997;Ziemann et al, 1998a;Ziemann et al, 1998b), result in an expansion of the surrounding representations.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the effectiveness of previously existing synapses can be dramatically modified and that new synapses can be formed. Many other studies showed that cortical sensorimotor representations can be reorganized after peripheral damage [26], after amputation [27][28][29], after spinal cord injury [30][31][32], after transient deafferentiation [33], after ischaemic nerve block [34], after stroke [35] and even after arthritis-like inflammation [36]. Spear [37] showed that neurons in the lateral supra-sylvian gyrus that normally are unresponsive to specific visual input can become responsive to these stimuli in the event that normal visual cortical areas are impaired.…”
Section: Essentials Of Adaptabilitymentioning
confidence: 99%